Legal Pluralism in Contracts: Reconstruction of the Principle of Freedom of Contract for the Harmonization of Customary and National Law - Agustini, Shenti; Bajury, Mimi Sintia Mohd; Agustianto, Agustianto; Jaya, Febri; Fitri, Winda (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article examines the normative tension between the principle of freedom of contract in national civil law and the practice of customary agreements within indigenous communities. In the Indonesian legal system, contractual relations are generally constructed on an individualistic and formal legal framework, while customary agreements are rooted in communal values, unwritten norms, and local wisdom. Within the perspective of legal pluralism, the coexistence of these different legal orders often generates challenges in terms of recognition, validity, and legal enforcement. Purposes of the Research: The purpose of this research is to identify the normative points of tension between the doctrine of freedom of contract and the practice of customary agreements and to formulate a conceptual model for integrating these norms within the national civil law system through the perspective of legal pluralism. Methods of the Research: This research employs a normative juridical method using statute, conceptual, and comparative approaches. Legal materials consist of primary legal sources such as legislation and secondary materials including legal doctrines and scholarly writings related to civil law, customary law, and legal pluralism. Results of the Research: The findings reveal that the normative tension between the principle of freedom of contract and customary agreements stems from differences in legal subjects, consent, evidentiary standards, bargaining positions, and legal authority. To address these tensions, this study proposes an integration model through the reconstruction of the freedom of contract doctrine to accommodate communal values, a progressive approach recognizing customary agreements as legally valid, adaptive evidentiary mechanisms that incorporate customary proof, and legal pluralism-based harmonization between national civil law and customary law. These models preserve legal certainty while strengthening recognition of indigenous communities' living law.